PENDUGAAN LAJU EROSI TANAMAN SERAI WANGI (Cymbopogon nardus L.) PADA LAHAN PASCA TAMBANG - Devi Fitri Yanti; Irdika mansyur; Omo Rusdiana; Hifzil Kirmi (The University of Lampung, 2020)
Human activities in utilizing natural resources, including in coal activities without conservation measures will cause environmental damage, among others, the danger of erosion. One of the impacts of erosion is declining land productivity, so it is necessary to follow up in the form of rehabilitation of forests and land. This research aims to identify the estimation of erosion rate on the post-mining land of PT Berau Coal planted with citronella grass and the financial feasibility of citronella grass revegetation. The field method is conducted through surveys and observations to determine the length of slope and slope of a slope. Determination of the sampling point in this study using stratified sampling technique. Sampling point is all revegetation land planting citronella grassand cover crop there are 6 sampling points. The observed parameters include soil properties, erosion predictions occurring, erosivity factors, soil erosiveness, slope length and slope, crop factor and land conservation, tolerable erosion, and danger level erosion. The results showed the magnitude of the value of the alleged erosion rate by using the USLE method at the research site planted by the seraiwangi plants has considerable erosion potential ranging from a 12% slope of 891.98 tons/ha/yr while the highest soil erosion at the Pit H4 SW L study site at a 30% slope of 3060.10 tons/ha/yr.